Antidiabetic Activities of Muntingia Calabura L. Leaves Water Extract in Type 2 Diabetes Mellitus Animal Models - Widhya Aligita; Elis Susilawati; Ika Kurnia Sukmawati; Lusi Holidayanti; Jejen Riswanti (The Indonesian Biomedical Journal, 2018)
BACKGROUND: Diabetes Mellitus (DM) is a heterogeneous group of disorders characterized by increasing blood glucose levels caused by insufficiency of insulin hormone production and activities. There are significant increases in DM case every year in Indonesia, as a consequent, alternative and better drug is needed to be developed. One of the plants that were often used as traditional medicine for DM in Indonesia was Muntingia carabula L. (kersen) leaf. The aim of this research was to evaluate the antidiabetes activity of M. carabula leaves.METHODS: This study was conducted in vivo by evaluating the antidiabetic activity of M. carabula leaf water extract on two animal models, those are insulin deficiency and insulin resistant model animal. The insulin deficiency animal model was developed by aloxan administration at dose of 50 mg/Kg body weight (bw) intravenously. While the insulin resistance animal model was developed by lipid emulsion administration at dose of 0.42 mL/20 grams bw orally. Both groups were randomly devided into 6 groups, which are negative control group, positive control group, standard drug group (glybenclamide 0.65 mg/Kg bw or  metformin 135 mg/Kg bw), and extract groups at dose of 100, 200 and 400 mg/Kg bw. Parameters which were evaluated are fasting blood glucose (FBG) levels for insulin deficiency models and values of constant of insulin tolerance (KITT) for insulin resistant models.RESULTS: In insulin deficient model group, administration of glibenclamide lower the FBG by 43%, furthermore, the extract of M. calabura at doses of 100, 200 and 400 mg/Kg bw also lower the FBG by 13%, 22% and 29%, subsequently. In insulin resistant models, metformin increased the value of KITT from less than 0.5 to 2.91, and administration of the extract at doses of 400, 200 and 100 mg/Kg bw also increased the KITT value to 2.31, 1.57, 1.13, respectively.CONCLUSION: The conclusion was M. carabula leaves water extract with dose of 400 mg/Kg bw had the antidiabetic activities with mechanisms to lower blood glucose level, regenerate pancreatic β cells, and increase insulin sensitivity.KEYWORDS: diabetes mellitus, kersen leaves, Muntingia calabura L., insulin deficiency, insulin resistance